2017
DOI: 10.1177/1753193417728405
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of active pick-up function in patients with total brachial plexus avulsion injuries

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 16 publications
(20 reference statements)
0
11
0
Order By: Relevance
“…The search for the optimum method of reconstruction continues. Multiple nerve transfer methods for total brachial plexus avulsion injuries have been shown to restore useful upper limb function, including active pick-up and protective sensation (Li et al, 2018;Wang et al, 2013). Their method includes the transfer of the accessory nerve onto the suprascapular nerve, CC7 nerve onto the lower trunk directly, musculocutaneous nerve with interpositional bridging by the medial antebrachial cutaneous nerve arising from the lower trunk and the phrenic nerve onto the posterior division of the lower trunk.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The search for the optimum method of reconstruction continues. Multiple nerve transfer methods for total brachial plexus avulsion injuries have been shown to restore useful upper limb function, including active pick-up and protective sensation (Li et al, 2018;Wang et al, 2013). Their method includes the transfer of the accessory nerve onto the suprascapular nerve, CC7 nerve onto the lower trunk directly, musculocutaneous nerve with interpositional bridging by the medial antebrachial cutaneous nerve arising from the lower trunk and the phrenic nerve onto the posterior division of the lower trunk.…”
Section: Discussionmentioning
confidence: 99%
“…The patients who achieved useful recovery were selected for secondary reconstruction to restore active pickup. Forty patients achieved finger extension and flexion reached more than M3 in 15 (38%) and 25 (63%) patients, respectively (Li et al, 2018). Only 25% of patients achieved active pick-up function, which is defined as actively touching a target object without the help of the contralateral hand, grabbing it, moving it to another place and putting it down (Li et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary and secondary reconstructive efforts were agreed to be elbow flexion and shoulder stability. For the remaining functions to be reconstructed, the treatment strategies varied as well as the preferences for use of phrenic nerve and CC7 (Figure 1) (Li et al, 2018;Sammer et al, 2012;Wang and Xue, 2014;Wang et al, 2013Wang et al, , 2016Wang et al, , 2021, FFMT (Figure 2) (Adams et al, 2009;Barrie et al, 2004;Chim et al, 2014;Giuffre et al, 2012;Maldonado et al, 2016aMaldonado et al, , 2017aMaldonado et al, , 2017b, reimplantation of roots into the spinal cord (Figure 3) (Carlstedt, 2009;Carlstedt et al, 2000Carlstedt et al, , 2004Htut et al, 2007) and shoulder arthrodesis.…”
Section: The Survey Methods and Expert Panelmentioning
confidence: 99%
“…Finger flexion [42] or elbow extension [43] can be restored by nerve transfer or biceps-to-triceps transfers for patients with tetraplegia. Nerve transfer also could restore active picking-up function for patients with total brachial plexus avulsion injuries [44]. Zheng et al in a single-center randomized controlled trial reported that transferring the C7 nerve from the nonparalyzed side to the paralyzed side of the arm could leads to greater improvement in function and reduction of spasticity for patients with chronic cerebral injury for more than 5 years [45].…”
Section: Neurorestorative Surgerymentioning
confidence: 99%